Organizações criminosas em Mato Grosso à luz da associação diferencial : o caso dos "salves" determinados pelo Comando Vermelho na periferia de Cuiabá - Trindade, Alana Derlene Sousa Cardoso (2021)
The present work analyzes the social implications of the acts of violence resulting from the "salves" determined by the Comando Vermelho of Mato Grosso (CVMT) and executed in the peripheral regions of Cuiabá in the years 2017 and 2018, having as a theoretical reference the Symbolic Interactionism and the Theory of Differential Association. It presents the description of the emergence from CVMT in the Central Penitentiary of the State (PCE) in Cuiabá, registered in judicial processes and police investigations, under the eyes of the public security operators and the Judiciary, through decisions that mark the CVMT as a criminal organization under the terms of Law n. 12,850/2013. Outlining the legal and sociological aspects of criminal organizations and a brief history of the Comando Vermelho in Rio de Janeiro and the Primeiro Comando da Capital (PCC) in São Paulo, it recognizes the CVMT as a franchise for the Rio de Janeiro‘s Command. And studying cases of ―salves‖ and their public repercussions, it identifies digital social networks as a form of symbolic interaction capable of promoting the learning of the Differential Association and points out the territorial occupation and control of criminal activity as claimed by the CVMT. Its methodology is the analysis of documentary and bibliography contents, as a strategy the case study of the CVMT as a criminal organization active especially in Cuiabá, and as the main technique of collection data two categories of documents: the judicial processes and police investigations, in addition to anonymous interviews of public security operators.